Actor-network theory and socio-legal objects: analysing TRIPS and pharmaceutical patents in the Republic of Djibouti - Cloatre, Emilie (2006)
This research analyses the role and action of the Trade Related Intellectual Property Agreements (TRIPS) and pharmaceutical patents in the public health network of Djibouti, by using an approach largely inspired by actor-network theory (ANT). In doing so, it addresses issues that run beyond the specificities of this case study and relate more broadly to the relevance of ANT to socio-legal analysis.